Composite cathode material for sulfide solid-state battery and preparation method and application thereof
Patent Information
- Application Number
- CN202311347428.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-10-18
AI Technical Summary
其中固相研磨法制备的硫化物复合正极常存在各组分分散不均匀、有效接触面积低,正极活性物质的形貌/结构破坏严重,正极活性物质/硫化物固态电解质固-固界面直接接触以及界面副反应持续等问题
[0031](1)本发明利用混合溶液合成法,促使硫化物电解质的各前驱体组分完全溶解于有机胺与有机硫醇的混合溶液中,获得硫化物电解质的前驱液并通过将正极活性物质、导电剂加入硫化物电解质前驱液中以及加热、搅拌处理,实现正极活性物质、导电剂与硫化物电解质前驱体组分的均匀混合与分散。在物理/化学作用下实现部分硫化物电解质前驱体组分通过TM-O-P-S间的作用力吸附在正极活性物质颗粒表面,通过后续真空干燥、高温焙烧等处理步骤,促使高比容量正极活性物质材料表面预先形成含有Li-TM-O-P-S组分的均匀界面缓冲层物质,有效避免了高比容量正极活性物质与硫化物电解质的直接接触,抑制了界面副反应,提高了高比容量正极活性物质与硫化物电解质的界面稳定性。
Smart Images

Figure CN117410463B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery electrode materials technology, specifically to a sulfide solid-state battery composite cathode material, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries, as efficient and green energy storage and conversion devices, are widely used in electronic products, electric vehicles, and large-scale energy storage. In recent years, with increasing demands for energy density and safety, liquid lithium-ion batteries have struggled to meet these requirements. Therefore, all-solid-state lithium battery technology based on different types of solid electrolytes has been developed and holds promise for solving these challenges. Among these, all-solid-state battery technology using inorganic sulfides as solid electrolytes has received widespread attention and extensive research. This is because sulfide electrolytes not only possess ionic conductivity comparable to liquid electrolytes but also offer advantages such as low Young's modulus, high thermal stability, and mild synthesis conditions. Therefore, combining sulfide electrolytes with high-specific-capacity positive electrode active materials and applying them to all-solid-state battery systems holds promise. This not only improves the energy density and safety of solid-state batteries but also achieves tight contact within the sulfide solid electrolyte and between the positive electrode active material and the sulfide electrolyte, facilitating rapid ion transport, reducing solid-solid interface impedance, and improving electrochemical performance.
[0003] However, it should be noted that the composite cathode material, composed of positive electrode active material, sulfide electrolyte, and conductive agent, is the decisive factor affecting the electrochemical performance of sulfide solid-state batteries. The degree of dispersion, contact mode, contact area, and porosity of the components within the composite cathode material all have a significant impact on the interfacial stability of the positive electrode active material / sulfide electrolyte, the ion transport rate, and the utilization rate of the active material, thereby affecting the electrochemical performance of the sulfide solid-state battery.
[0004] Currently, methods for preparing sulfide composite cathode materials include solid-phase milling and liquid-phase methods. Solid-phase milling often results in uneven dispersion of components, low effective contact area, severe damage to the morphology / structure of the cathode active material, direct solid-solid interface contact between the cathode active material and the sulfide solid electrolyte, and persistent interfacial side reactions. Liquid-phase methods primarily use low-polarity solvents such as anhydrous ethanol, ethyl propionate, acetonitrile, and toluene. While these solvents facilitate uniform dispersion and contact between the electrode and electrolyte, their limited solubility for the sulfide electrolyte or its precursor components and their tendency to trigger solid-liquid interfacial side reactions during preparation lead to increased impurity content and decreased ionic conductivity in the sulfide electrolyte after liquid-phase processing. Furthermore, this type of liquid-phase process also cannot avoid direct solid-solid contact between the electrode and electrolyte, similarly triggering persistent interfacial side reactions, increasing interfacial impedance, hindering lithium-ion transport, and affecting the capacity of the sulfide solid-state battery.
[0005] Therefore, developing novel composite cathode materials, increasing the effective interfacial contact area between the cathode active material and the sulfide electrolyte, constructing an efficient ion transport network, and improving the interfacial stability between the cathode active material and the sulfide electrolyte are crucial for the electrochemical performance of sulfide solid-state batteries. Summary of the Invention
[0006] The main objective of this invention is to overcome the shortcomings of the prior art and provide a composite cathode material for sulfide solid-state batteries, its preparation method, and its application.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A composite cathode material for sulfide solid-state batteries is provided. The composite cathode material is formed by generating an interface buffer layer of Li-TM-OSP (TM = Ni, Co, Mn) on the surface of cathode active material particles using a mixed solution method, and growing crystalline sulfides in situ in the gaps between the particles and the interface buffer layer to form a three-dimensional ionic composite cathode active material.
[0009] The aforementioned three-dimensional ion composite positive electrode active material possesses a fast lithium-ion transport network that is spatially distributed in a three-dimensional manner.
[0010] The composite cathode material is formed by generating an interface buffer layer of Li-TM-OSP (TM = Ni, Co, Mn) on the surface of cathode active material particles and conductive agent using a mixed solution method. Crystalline sulfides are grown in situ in the gaps between the particles and the interface buffer layer to form a three-dimensional ionic composite cathode active material. At the same time, in the presence of the conductive agent, an anisotropic electron transport network is formed between the composite cathode active materials in a bridging manner, which is a composite cathode active material with a three-dimensional carrier transport network.
[0011] The composite cathode active material with the aforementioned three-dimensional carrier transport network has a fast lithium-ion transport network with spatial three-dimensional distribution and an anisotropic electron transport network with spatial three-dimensional distribution.
[0012] The mass ratio of positive electrode active particles, crystalline sulfide and conductive agent in the composite positive electrode material is 30-90:70-10:0-5.
[0013] The positive electrode active material particles are high-specific-capacity positive electrode active materials; the high-specific-capacity positive electrode active materials are lithium cobalt oxide (LiCoO2) and lithium nickel cobalt manganese oxide (LiNiO2). a Co b Mn 1-a-b O2, 0.6≤a<1) and lithium-rich manganese-based matrix oxides (xLi2MnO3·(1-x)LiNi) a Co b Mn 1-a-b One or more of the following: O2, 0 < x < 1, 0.3 ≤ a < 1; the conductive agent is one or more of the following: conductive carbon black (SP), carbon nanotubes, vapor-grown carbon fiber (VGCF), and graphene.
[0014] A method for preparing the composite cathode material for a sulfide solid-state battery, wherein the composite cathode material is formed by generating an interface buffer layer of Li-TM-OSP (TM = Ni, Co, Mn) on the surface of cathode active material particles using a mixed solution method, and growing crystalline sulfides in situ at the gaps between the particles and the interface buffer layer to form a three-dimensional ionic composite cathode active material.
[0015] Alternatively, the composite cathode material is formed by generating an interface buffer layer of Li-TM-OSP (TM = Ni, Co, Mn) on the surface of cathode active material particles and conductive agent using a mixed solution method, and growing crystalline sulfides in situ in the gaps between the particles and the interface buffer layer to form a three-dimensional ionic composite cathode active material. At the same time, in the presence of the conductive agent, the composite cathode active materials form an anisotropic electron transport network in a bridging manner, which is a composite cathode active material with a three-dimensional carrier transport network.
[0016] Furthermore, the precursor components required for in-situ growth of crystalline sulfides, positive electrode active material particles, or positive electrode active material particles and conductive agents are simultaneously added to a mixed solution. The strong nucleophilic effect of the mixed solution promotes the complete dissolution of each precursor component of the sulfide, forming a sulfide solid electrolyte precursor solution. The positive electrode active material particles or positive electrode active material particles and conductive agents are dispersed in the formed sulfide solid electrolyte precursor solution. After high-temperature calcination, an interface buffer layer containing Li-TM-OPS components is formed on the surface of the positive electrode active material particles. Crystalline sulfides (i.e., sulfide solid electrolyte particles) are distributed on the surface of the interface buffer layer and between the positive electrode active material particles. At the same time, in the presence of the conductive agent, an anisotropic electron transport network is formed between the composite positive electrode active materials in a bridging manner, which is a composite positive electrode active material with a three-dimensional carrier transport network.
[0017] In the preparation of composite positive electrode active materials, simple heating causes the strong nucleophilic forces of thioanions in the mixed solution to completely dissociate and dissolve the required precursor components of the sulfide electrolyte into the mixed solution, resulting in a sulfide electrolyte precursor component solution. The positive electrode active material particles, or positive electrode active material particles and conductive agents, are dispersed in the formed sulfide solid electrolyte precursor solution. Further heating, under physical / chemical action, causes some sulfide electrolyte precursor components to be adsorbed uniformly onto the surface of the positive electrode active material particles through the interaction forces between Co-OPS. Further calcination then causes a uniform interface buffer layer containing Li-Co-OPS components to be pre-formed on the surface of the high-specific-capacity positive electrode active material. Crystalline sulfide electrolyte Li3PS4 is then generated in situ between the interface buffer layer and the positive electrode active material particles, thus obtaining a composite positive electrode bulk material with a three-dimensional ion transport network prepared in situ by the mixed solution synthesis method. Simultaneously, when the raw materials contain conductive agents, the composite positive electrode active materials are further connected in a bridging manner to form an anisotropic electron transport network, resulting in a composite positive electrode active material with a three-dimensional carrier transport network.
[0018] The sulfide solid electrolyte precursor solution is one or more of sulfur-containing lithium salts, sulfur-containing phosphorus salts, halogen-containing lithium salts, or sulfur-containing transition metal salts, which are added to a mixed solution and stirred at 40-80°C for 1-5 hours to obtain the solution; wherein the mixed solution is a mixture of organic amines and organic thiols in a volume ratio of 100:5-40.
[0019] To go even further:
[0020] (1) Add the positive electrode active material particles and the conductive agent to the precursor liquid of the sulfide electrolyte at a mass ratio of 30-90:0-5, and stir the reaction at 40-80℃ for 1-5 hours to obtain a solid-liquid mixture in which the positive electrode active material particles and the conductive agent are completely dispersed in the precursor liquid of the sulfide electrolyte.
[0021] (3) The obtained solid-liquid mixture is vacuum dried at 50-100℃ for 5-15 hours and calcined at 500-800℃ for 5-20 hours. First, an interface buffer layer containing Li-TM-OPS components is formed and coated on the surface of high specific capacity positive electrode active material particles. Then, crystalline sulfides are formed in situ on the surface of the interface buffer layer and between the positive electrode active material particles by the precursor components of the sulfide electrolyte. At the same time, in the presence of a conductive agent, an anisotropic electron transport network is formed between the composite positive electrode active materials in a bridging manner. Then, the mixture is ground to obtain a composite positive electrode active material with a uniform particle size distribution and a three-dimensional carrier transport network, which is prepared in situ by the mixed solution synthesis method.
[0022] The sulfur-containing lithium salt is Li2S; the sulfur-containing phosphorus salt is P2S5; and the halogen-containing lithium salt is one or more of LiCl, LiI, and LiBr.
[0023] The organic amine is one or more of ethylenediamine, n-propylamine, propylenediamine, and n-butylamine, and the organic thiol is one or more of ethanethiol, ethylenedithiol, propylenedithiol, propylenedithiol, benzenethiol, and p-phenylenediol.
[0024] The precursor materials for the aforementioned positive electrode active material particles are prepared using solid-state synthesis or co-precipitation methods. These precursor materials are then mixed and ground with lithium salts (lithium carbonate, lithium hydroxide) at a molar ratio of 1:1.05, followed by lithiation under high-temperature calcination conditions. This process ultimately yields high-specific-capacity lithium cobalt oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese-based layered oxide positive electrode materials. The precursor materials can be one or more of transition metal carbonates (TMCO3), transition metal hydroxides (TM(OH)2), or transition metal oxides (TMO), where TM = Ni, Co, Mn.
[0025] An application of the aforementioned composite cathode material, specifically its use in the preparation of sulfide electrolyte all-solid-state batteries.
[0026] A sulfide electrolyte all-solid-state battery, the battery comprising the composite cathode material for the sulfide solid-state battery.
[0027] The negative electrode of the sulfide electrolyte all-solid-state battery is one of lithium metal negative electrode, lithium-indium negative electrode, carbon negative electrode, silicon negative electrode, and silicon-carbon negative electrode.
[0028] The sulfide solid electrolytes in solid-state batteries are Li6PS5Cl, Li3PS4, Li6PS5Br, and Li 10 GeP2S 12 One or more of them.
[0029] In preparing a sulfide electrolyte all-solid-state battery, firstly, 80 mg of sulfide solid electrolyte Li6PS5Cl powder material is placed in a solid-state battery mold with a diameter of 10 mm and a pressure of 200 MPa is applied to form a sulfide electrolyte layer. Then, 10 mg of the high-specific-capacity composite positive electrode is placed from one side of the sulfide solid electrolyte layer and a pressure of 800 MPa is applied. Next, a certain mass of negative electrode material is placed on the other side of the sulfide solid electrolyte layer and a pressure of 200 MPa is applied. Finally, the sulfide electrolyte solid-state battery is prepared using a sealing ring and a pressure mechanical clamp.
[0030] Compared with the prior art, the beneficial effects of the technical solution of the present invention are as follows:
[0031] (1) This invention utilizes a mixed solution synthesis method to ensure that all precursor components of the sulfide electrolyte are completely dissolved in a mixed solution of organic amines and organic thiols, thereby obtaining a precursor solution of the sulfide electrolyte. By adding the positive electrode active material and conductive agent to the sulfide electrolyte precursor solution, and then heating and stirring, uniform mixing and dispersion of the positive electrode active material, conductive agent, and sulfide electrolyte precursor components are achieved. Under physical / chemical action, some sulfide electrolyte precursor components are adsorbed onto the surface of the positive electrode active material particles through the interaction forces between TM-OPS. Subsequent vacuum drying and high-temperature calcination processes further promote the pre-formation of a uniform interfacial buffer layer containing Li-TM-OPS components on the surface of the high-specific-capacity positive electrode active material. This effectively avoids direct contact between the high-specific-capacity positive electrode active material and the sulfide electrolyte, suppresses interfacial side reactions, and improves the interfacial stability between the high-specific-capacity positive electrode active material and the sulfide electrolyte.
[0032] (2) This invention utilizes a mixed solution synthesis method and subsequent vacuum drying and high-roasting treatment to generate crystalline sulfide electrolyte in situ in the gaps between particles and the interface buffer layer. This achieves full surface-to-surface contact between the high specific capacity positive electrode active material and the sulfide electrolyte, enabling the construction of an efficient three-dimensional lithium-ion transport network. This is beneficial to improving the utilization rate of the positive electrode active material and increasing the energy density of the all-solid-state battery.
[0033] (3) The present invention utilizes a mixed solution synthesis method to prepare high specific capacity composite cathodes in situ, avoiding the problems of uneven dispersion of components, low effective contact area, severe damage to the morphology / structure of cathode active material, and continuous side reactions at the electrode / electrolyte solid-solid interface that exist in the solid-phase method for preparing composite cathodes. At the same time, it also solves the problems of incomplete dissolution of sulfide electrolyte or precursor components, severe solid-liquid interface side reactions, high impurity content of sulfide electrolyte, and low ionic conductivity that exist in the previous liquid-phase method for preparing composite cathodes.
[0034] (4) The present invention utilizes the mixed solution synthesis method to prepare composite cathodes in situ, which has the advantages of simple and mild preparation conditions, and can also increase the content of cathode active material in composite cathodes, which is beneficial to improving the energy density of solid-state batteries. Attached Figure Description
[0035] Figure 1 The diagram shows (a) the nucleophilic reaction of thioanions on sulfide precursor components in the organic amine-organothiol mixed solution in Example 1, and (b) an optical photograph showing the complete dissolution of the sulfide electrolyte precursor components in the organic amine-organothiol mixed solution.
[0036] Figure 2 The images shown in Example 1 are: (a) XPS analysis of the surface of the positive active material in the composite positive electrode material; (b) SEM image of the composite positive electrode powder material; (c) XRD pattern of the composite positive electrode material and the sulfide electrolyte; and (d) schematic diagram of the composite positive electrode material.
[0037] Figure 3 The images shown are (a) XPS and (b) SEM images of the composite cathode powder material synthesized by solid-state method in Comparative Example 1.
[0038] Figure 4 The first charge-discharge curves are for a sulfide solid-state battery assembled using the composite cathode material prepared in Example 1.
[0039] Figure 5 Cycle performance testing of a sulfide solid-state battery assembled with the composite cathode material prepared in Example 1.
[0040] Figure 6 The first charge-discharge curves of the sulfide solid-state battery assembled using the composite cathode material prepared in Comparative Example 1 are shown.
[0041] Figure 7 Cycle performance testing of sulfide solid-state batteries assembled from composite cathode materials synthesized by solid-state method in Comparative Example 1. Detailed Implementation
[0042] This invention utilizes lithium-rich manganese-based matrix oxide single crystals (0.5Li₂MnO₃·0.5LiNi) to respectively... 1 / 3 Co 1 / 3 Mn 1 / 3 O2), lithium cobalt oxide (LiCoO2) single crystal, lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1O2 polycrystalline silicon is used as the positive electrode material, Li6PS5Cl and Li3PS4 are used as sulfide electrolytes, vapor-grown fiber (VGCF), graphene, and conductive carbon black (SP) are used as conductive agents, and lithium-indium alloy is used as the negative electrode. The composite positive electrode material is prepared by mixed solution synthesis method, solid-phase synthesis method, and solution treatment method, respectively. The present invention will be further described below with reference to the accompanying drawings and embodiments:
[0043] Example 1
[0044] This embodiment provides a composite cathode material for sulfide solid-state batteries with a three-dimensional ion transport network, comprising a lithium-rich manganese-based single-crystal cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based single-crystal cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0045] This embodiment also provides a method for in-situ preparation of lithium-rich manganese-based sulfide composite cathode materials with a three-dimensional ion transport network using a mixed solution synthesis method. The specific steps are as follows:
[0046] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li₂S, and 111.14 mg P₂S₅ were simultaneously added to a mixed solution of 50 ml ethylenediamine and 10 ml ethanethiol. The mixture was stirred at 65°C for 2.5 hours. The strong nucleophilic interaction of the thioanions in the mixed solution caused the Li₂S, P₂S₅, and LiCl components to completely dissociate and dissolve in the mixed solution, yielding a precursor solution for the sulfide electrolyte. Figure 1 As shown.
[0047] Step 2: 178.9 mg of lithium-rich manganese-based single crystal cathode material and 13.42 mg of VGCF were simultaneously added to the precursor component solution of the above-mentioned sulfide electrolyte. The mixture was magnetically stirred at 65°C for 3 hours. Under physical / chemical action, some of the sulfide electrolyte precursor components were uniformly adsorbed onto the surface of the cathode active material particles through the interaction force between TM-OPS, and a solid-liquid mixture was obtained.
[0048] Step 3: The obtained solid-liquid mixture is transferred to a vacuum tube furnace connected to an argon-filled glove box and vacuum-dried at 80°C for 10 hours. Then, the temperature is increased to 700°C at a rate of 2°C / min and calcined for 15 hours. This process promotes the pre-formation of a uniform interfacial buffer layer containing Li-TM-OPS components on the surface of the high-capacity positive electrode active material. This leads to the in-situ formation of crystalline sulfide electrolyte Li6PS5Cl between the interfacial buffer layer and the positive electrode active material particles. Simultaneously, it promotes the construction of anisotropic electron transport networks between the positive electrode active material particles through the bridging effect of conductive agents. Figure 2 As shown in a and b, a composite cathode bulk material with a three-dimensional carrier transport network was obtained by in-situ preparation using a mixed solution synthesis method.
[0049] Step 4: The obtained composite cathode material block is manually ground in a glove box using a mortar and pestle for 10 minutes to obtain a composite cathode powder material in which crystalline Li6PS5Cl is uniformly coated on the surface of the interface buffer layer and uniformly filled in the gaps between the lithium-rich manganese-based single crystal cathode material particles. The in-situ generated crystalline Li6PS5Cl electrolyte has a particle size of 0.4-1 μm and a coating thickness of 2-4 μm.
[0050] Step 5: In an argon-filled glove box, 2.297g Li₂S, 2.222g P₂S₅, and 0.848g LiCl were placed in a ball mill jar, along with 20 10mm diameter zirconia grinding balls. The mixture was ball-milled at 600 rpm for 200 minutes. Then, under an argon atmosphere, the mixture was calcined at 550℃ for 8 hours to obtain crystalline sulfide electrolyte Li₆PS₅Cl block material. Finally, the obtained Li₆PS₅Cl block material was ground for 30 minutes in a glove box to obtain laboratory-prepared Li₆PS₅Cl electrolyte powder material for use as the electrolyte layer in sulfide solid-state batteries.
[0051] Step 6: Assemble the lithium-rich manganese-based sulfide composite cathode obtained in Step 4, the Li6PS5Cl sulfide electrolyte powder material obtained in Step 5, and the lithium-indium alloy anode material into a sulfide solid-state battery in an argon-filled glove box.
[0052] Step 7: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under the specified rate conditions. Figure 4 , 5 As shown, the solid-state battery assembled using a composite cathode prepared in situ via a mixed solution synthesis method achieves a first-cycle discharge capacity of 155.4 mAh g⁻¹. -1 The initial coulombic efficiency was 68.6%, and after 45 cycles, the solid-state battery still maintained a discharge specific capacity of 192.3 mAh g. -1 .
[0053] Example 2
[0054] This embodiment provides a composite cathode material for sulfide solid-state batteries with a three-dimensional ion transport network, comprising a lithium-rich manganese-based single-crystal cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based single-crystal cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0055] This embodiment also provides a method for in-situ preparation of lithium-rich manganese-based sulfide composite cathode materials with a three-dimensional ion transport network using a mixed solution synthesis method. The specific steps are as follows:
[0056] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, and 111.14 mg P2S5 were simultaneously added to a mixed solution of 50 ml ethylenediamine and 10 ml ethanethiol. The mixture was stirred at 65 °C for 2.5 hours. Under the strong nucleophilic force of the thioanion in the mixed solution, the Li2S, P2S5, and LiCl components were completely dissociated and dissolved in the mixed solution, thus obtaining the precursor solution of the sulfide electrolyte.
[0057] Step 2: 178.9 mg of lithium-rich manganese-based single crystal cathode material and 13.42 mg of VGCF were simultaneously added to the precursor component solution of the above-mentioned sulfide electrolyte. The mixture was magnetically stirred at 65°C for 3 hours. Under physical / chemical action, some of the sulfide electrolyte precursor components were uniformly adsorbed onto the surface of the cathode active material particles through the interaction force between TM-OPS, and a solid-liquid mixture was obtained.
[0058] Step 3: The obtained solid-liquid mixture is transferred to a vacuum tube furnace connected to a glove box filled with argon gas and vacuum dried at 80°C for 10 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min and calcined at high temperature for 15 hours to promote the pre-formation of a uniform interface buffer layer containing Li-TM-OPS components on the surface of the high specific capacity positive electrode active material. Then, crystalline sulfide electrolyte Li6PS5Cl is generated in situ in the interface buffer layer and the gaps between the positive electrode active material particles, thereby obtaining a composite positive electrode bulk material with a three-dimensional ion transport network prepared in situ by the mixed solution synthesis method.
[0059] Step 4: The obtained composite cathode material block is manually ground in a glove box using a mortar and pestle for 10 minutes to obtain a composite cathode powder material in which crystalline Li6PS5Cl is uniformly coated on the surface of the interface buffer layer and uniformly filled in the gaps between the lithium-rich manganese-based single crystal cathode material particles. The in-situ generated crystalline Li6PS5Cl electrolyte has a particle size of 0.4-1 μm and a coating thickness of 2-4 μm.
[0060] Step 5: Assemble the lithium-rich manganese-based sulfide composite cathode obtained in Step 4, the commercially purchased Li6PS5Cl sulfide electrolyte powder material, and the lithium-indium alloy anode material into a sulfide solid-state battery in an argon-filled glove box.
[0061] Step 6: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under various rate conditions. The solid-state battery assembled from a composite cathode prepared in situ using a mixed solution synthesis method achieved a first-cycle discharge capacity of 150.1 mAh g⁻¹. -1 The initial coulombic efficiency was 67.2%, and after 45 cycles, the solid-state battery still maintained a discharge specific capacity of 186.2 mAh g. -1 .
[0062] Example 3
[0063] This embodiment provides a composite cathode material for sulfide solid-state batteries with a three-dimensional ion transport network, comprising a lithium-rich manganese-based single-crystal cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based single-crystal cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0064] This embodiment also provides a method for in-situ preparation of lithium-rich manganese-based sulfide composite cathode materials with a three-dimensional ion transport network using a mixed solution synthesis method. The specific steps are as follows:
[0065] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, and 111.14 mg P2S5 were simultaneously added to a mixed solution of 50 ml ethylenediamine and 5 ml ethanethiol. The mixture was stirred at 65 °C for 2.5 hours. Under the strong nucleophilic force of the thioanion in the mixed solution, the Li2S, P2S5, and LiCl components were completely dissociated and dissolved in the mixed solution, thus obtaining the precursor solution of the sulfide electrolyte.
[0066] Step 2: 178.9 mg of lithium-rich manganese-based single crystal cathode material and 13.42 mg of VGCF were simultaneously added to the precursor component solution of the above-mentioned sulfide electrolyte. The mixture was magnetically stirred at 65°C for 3 hours. Under physical / chemical action, some of the sulfide electrolyte precursor components were uniformly adsorbed onto the surface of the cathode active material particles through the interaction force between TM-OPS, and a solid-liquid mixture was obtained.
[0067] Step 3: The obtained solid-liquid mixture is transferred to a vacuum tube furnace connected to a glove box filled with argon gas and vacuum dried at 80°C for 10 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min and calcined at high temperature for 15 hours to promote the pre-formation of a uniform interface buffer layer containing Li-TM-OPS components on the surface of the high specific capacity positive electrode active material. Then, crystalline sulfide electrolyte Li6PS5Cl is generated in situ in the interface buffer layer and the gaps between the positive electrode active material particles, thereby obtaining a composite positive electrode bulk material with a three-dimensional ion transport network prepared in situ by the mixed solution synthesis method.
[0068] Step 4: The obtained composite cathode material block is manually ground in a glove box using a mortar and pestle for 10 minutes to obtain a composite cathode powder material in which crystalline Li6PS5Cl is uniformly coated on the surface of the interface buffer layer and uniformly filled in the gaps between the lithium-rich manganese-based single crystal cathode material particles. The in-situ generated crystalline Li6PS5Cl electrolyte has a particle size of 0.4-1 μm and a coating thickness of 2-4 μm.
[0069] Step 5: Assemble the lithium-rich manganese-based sulfide composite positive electrode obtained in Step 4, the Li6PS5Cl sulfide electrolyte powder material prepared in the laboratory in Step 5 of Example 1, and the lithium-indium alloy negative electrode material into a sulfide solid-state battery in an argon-filled glove box.
[0070] Step 6: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under various rate conditions. The solid-state battery assembled from a composite cathode prepared in situ using a mixed solution synthesis method achieved a first-cycle discharge capacity of 149.6 mAh g⁻¹. -1 The initial coulombic efficiency was 66.3%, and after 45 cycles, the solid-state battery still maintained a discharge specific capacity of 173.2 mAh g. -1 .
[0071] Example 4
[0072] This embodiment provides a composite cathode material for sulfide solid-state batteries with a three-dimensional ion transport network, comprising a lithium-rich manganese-based single-crystal cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based single-crystal cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0073] This embodiment also provides a method for in-situ preparation of lithium-rich manganese-based sulfide composite cathode materials with a three-dimensional ion transport network using a mixed solution synthesis method. The specific steps are as follows:
[0074] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, and 111.14 mg P2S5 were simultaneously added to a mixed solution of 50 ml ethylenediamine and 15 ml ethanethiol. The mixture was stirred at 65 °C for 2.5 hours. Under the strong nucleophilic force of the thioanion in the mixed solution, the Li2S, P2S5, and LiCl components were completely dissociated and dissolved in the mixed solution, thus obtaining the precursor solution of the sulfide electrolyte.
[0075] Step 2: 178.9 mg of lithium-rich manganese-based single crystal cathode material and 13.42 mg of VGCF were simultaneously added to the precursor component solution of the above-mentioned sulfide electrolyte. The mixture was magnetically stirred at 65°C for 3 hours. Under physical / chemical action, some of the sulfide electrolyte precursor components were uniformly adsorbed onto the surface of the cathode active material particles through the interaction force between TM-OPS, and a solid-liquid mixture was obtained.
[0076] Step 3: The obtained solid-liquid mixture is transferred to a vacuum tube furnace connected to a glove box filled with argon gas and vacuum dried at 80°C for 10 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min and calcined at high temperature for 15 hours to promote the pre-formation of a uniform interface buffer layer containing Li-TM-OPS components on the surface of the high specific capacity positive electrode active material. Then, crystalline sulfide electrolyte Li6PS5Cl is generated in situ in the interface buffer layer and the gaps between the positive electrode active material particles, thereby obtaining a composite positive electrode bulk material with a three-dimensional ion transport network prepared in situ by the mixed solution synthesis method.
[0077] Step 4: The obtained composite cathode material block is manually ground in a glove box using a mortar and pestle for 10 minutes to obtain a composite cathode powder material in which crystalline Li6PS5Cl is uniformly coated on the surface of the interface buffer layer and uniformly filled in the gaps between the lithium-rich manganese-based single crystal cathode material particles. The in-situ generated crystalline Li6PS5Cl electrolyte has a particle size of 0.4-1 μm and a coating thickness of 2-4 μm.
[0078] Step 5: Assemble the lithium-rich manganese-based sulfide composite cathode obtained in Step 4, the Li6PS5Cl sulfide electrolyte powder material prepared in the laboratory obtained in Example 5, and the lithium-indium alloy anode material into a sulfide solid-state battery in an argon-filled glove box.
[0079] Step 6: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under various rate conditions. The solid-state battery assembled using a composite cathode prepared in situ via a mixed solution synthesis method achieved a first-cycle discharge capacity of 148.7 mAh g⁻¹.-1 The initial coulombic efficiency was 66.1%, and after 45 cycles, the solid-state battery still maintained a discharge specific capacity of 177.6 mAh g. -1 .
[0080] Example 5
[0081] This embodiment provides a composite cathode material for sulfide solid-state batteries with a three-dimensional ion transport network, comprising a lithium-rich manganese-based monocrystalline cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent graphene, wherein the mass ratio of the lithium-rich manganese-based monocrystalline cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent graphene is 40:60:3.
[0082] This embodiment also provides a method for in-situ preparation of lithium-rich manganese-based sulfide composite cathode materials with a three-dimensional ion transport network using a mixed solution synthesis method. The specific steps are as follows:
[0083] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, and 111.14 mg P2S5 were simultaneously added to a mixed solution of 50 ml ethylenediamine and 5 ml ethylenedithiol. The mixture was stirred at 60 °C for 3 hours. Under the strong nucleophilic force of the thioanion in the mixed solution, the Li2S, P2S5, and LiCl components were completely dissociated and dissolved in the mixed solution, resulting in a sulfide electrolyte precursor component solution.
[0084] Step 2: 178.9 mg of lithium-rich manganese-based single crystal cathode material and 13.42 mg of graphene were simultaneously added to the precursor component solution of the above-mentioned sulfide electrolyte, and magnetically stirred at 60°C for 3 hours. Under physical / chemical action, some of the sulfide electrolyte precursor components were adsorbed uniformly on the surface of the cathode active material particles through the interaction force between TM-OPS, and a solid-liquid mixture was obtained.
[0085] Step 3: The obtained solid-liquid mixture is transferred to a vacuum tube furnace connected to a glove box filled with argon gas and vacuum dried at 80°C for 10 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min and calcined at high temperature for 15 hours to promote the pre-formation of a uniform interface buffer layer containing Li-TM-OPS components on the surface of the high specific capacity positive electrode active material. Then, crystalline sulfide electrolyte Li6PS5Cl is generated in situ in the interface buffer layer and the gaps between the positive electrode active material particles, thereby obtaining a composite positive electrode bulk material with a three-dimensional ion transport network prepared in situ by the mixed solution synthesis method.
[0086] Step 4: The obtained high specific capacity composite cathode material is manually ground in a glove box using a mortar and pestle for 10 minutes to obtain a composite cathode powder material in which each component is uniformly dispersed and crystalline Li6PS5Cl is uniformly coated on the surface of the interface buffer layer material and the gaps between the lithium-rich manganese-based single crystal cathode material particles. The in-situ generated crystalline Li6PS5Cl electrolyte has a particle size of 0.4-1 μm and a coating thickness of 2-4 μm.
[0087] Step 5: Assemble the lithium-rich manganese-based sulfide composite positive electrode from Step 4, the Li6PS5Cl sulfide electrolyte powder material obtained in Step 5 of Example 1, and the lithium-indium alloy negative electrode material into a sulfide solid-state battery in an argon-filled glove box.
[0088] Step 6: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under various rate conditions. The solid-state battery assembled from the composite cathode material prepared in situ using a mixed solution synthesis method achieved a first-cycle discharge capacity of 145.1 mAh g⁻¹. -1 The initial coulombic efficiency was 67.2%, and after 45 cycles, the solid-state battery still maintained a discharge specific capacity of 185.5 mAh g. -1 .
[0089] Example 6
[0090] This embodiment provides a composite cathode material for sulfide solid-state batteries with a three-dimensional ion transport network, comprising a lithium-rich manganese-based single-crystal cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based single-crystal cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0091] The specific steps are as follows:
[0092] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, and 111.14 mg P2S5 were simultaneously added to a mixed solution of 50 ml ethylenediamine and 10 ml benzenethiol. The mixture was stirred at 65 °C for 2.5 hours to promote the complete dissociation and dissolution of the Li2S, P2S5, and LiCl components in the mixed solution, thus obtaining the precursor solution of the sulfide electrolyte.
[0093] Step 2: 178.9 mg of lithium-rich manganese-based single crystal cathode material and 13.42 mg of VGCF were simultaneously added to the precursor component solution of the above-mentioned sulfide electrolyte. The mixture was magnetically stirred at 65°C for 3 hours. Under physical / chemical action, some of the sulfide electrolyte precursor components were uniformly adsorbed onto the surface of the cathode active material particles through the interaction force between TM-OPS, and a solid-liquid mixture was obtained.
[0094] Step 3: The obtained solid-liquid mixture is transferred to a vacuum tube furnace connected to a glove box filled with argon gas and vacuum dried at 80°C for 10 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min and calcined at high temperature for 15 hours to promote the pre-formation of a uniform interface buffer layer containing Li-TM-OPS components on the surface of the high specific capacity positive electrode active material. Then, crystalline sulfide electrolyte Li6PS5Cl is generated in situ in the interface buffer layer and the gaps between the positive electrode active material particles, thereby obtaining a composite positive electrode bulk material with a three-dimensional ion transport network prepared in situ by the mixed solution synthesis method.
[0095] Step 4: The obtained composite cathode material block is manually ground in a glove box using a mortar and pestle for 10 minutes to obtain a composite cathode powder material in which crystalline Li6PS5Cl is uniformly coated on the surface of the interface buffer layer and uniformly filled in the gaps between the lithium-rich manganese-based single crystal cathode material particles. The in-situ generated crystalline Li6PS5Cl electrolyte has a particle size of 0.4-1 μm and a coating thickness of 2-4 μm.
[0096] Step 5: Assemble the lithium-rich manganese-based sulfide composite cathode, the laboratory-prepared Li6PS5Cl sulfide electrolyte powder material, and the lithium-indium alloy anode material into a sulfide solid-state battery in an argon-filled glove box.
[0097] Step 6: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under various rate conditions. The solid-state battery assembled from a composite cathode prepared in situ using a mixed solution synthesis method achieved a first-cycle discharge capacity of 136.6 mAh g⁻¹. -1 The initial coulombic efficiency was 66.9%, and after 45 cycles, the solid-state battery still maintained a discharge specific capacity of 176.8 mAh g. -1 .
[0098] Example 7
[0099] This embodiment provides a composite cathode material for sulfide solid-state batteries with a three-dimensional ion transport network, comprising a high-voltage lithium cobalt oxide single-crystal cathode material, a Li3PS4 sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the high-voltage lithium cobalt oxide single-crystal cathode material, the Li3PS4 sulfide electrolyte, and the conductive agent VGCF is 70:30:0.
[0100] This embodiment also provides a method for in-situ preparation of lithium cobalt oxide sulfide composite cathode material with a three-dimensional ion transport network using a mixed solution synthesis method. The specific steps are as follows:
[0101] Step 1: In an argon-filled glove box, 68.92 mg Li2S and 111.14 mg P2S5 were simultaneously added to a mixed solution of 100 ml propylamine and 15 ml propanethiol. The mixture was stirred at 65 °C for 3 hours. Under the strong nucleophilic force of the thioanion in the mixed solution, the Li2S and P2S5 components were completely dissociated and dissolved in the mixed solution, resulting in a sulfide electrolyte precursor component solution.
[0102] Step 2: 626.25 mg of high-voltage lithium cobalt oxide single-crystal cathode material was simultaneously added to the precursor component solution of the above-mentioned sulfide electrolyte, and magnetically stirred at 65°C for 4 hours. Under physical / chemical action, some of the sulfide electrolyte precursor components were adsorbed uniformly onto the surface of the cathode active material particles through the interaction force between Co and OPS, resulting in a solid-liquid mixture.
[0103] Step 3: The obtained solid-liquid mixture is transferred to a vacuum tube furnace connected to a glove box filled with argon gas and vacuum dried at 90°C for 12 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min and calcined at high temperature for 15 hours to promote the pre-formation of a uniform interface buffer layer containing Li-Co-OPS components on the surface of the high specific capacity positive electrode active material. Then, crystalline sulfide electrolyte Li3PS4 is generated in situ in the interface buffer layer and the gaps between the positive electrode active material particles, thereby obtaining a composite positive electrode bulk material with a three-dimensional ion transport network prepared in situ by the mixed solution synthesis method.
[0104] Step 4: The obtained composite cathode material is manually ground in a glove box using a mortar and pestle for 10 minutes to obtain a composite cathode powder material in which each component is uniformly dispersed, and crystalline Li3PS4 is uniformly coated on the surface of the interface buffer layer and between the particles of the high-voltage lithium cobalt oxide single crystal cathode material. The Li3PS4 electrolyte particle size is 0.2-0.8 μm, and the coating thickness is 1-4 μm.
[0105] Step 5: Assemble the lithium cobalt oxide sulfide composite cathode obtained in Step 4, the Li6PS5Cl sulfide electrolyte powder material prepared in the laboratory in Step 5 of Example 1, and the lithium-indium alloy anode material into a sulfide solid-state battery in an argon-filled glove box.
[0106] Step 6: Incubate the assembled sulfide solid-state battery at 30°C and 3.0-4.5V (vs. Li). + / Li), 0.1C (1C=140mAg) -1 Charge-discharge tests were conducted under various rate conditions. The solid-state battery assembled using a composite cathode prepared in situ via a mixed solution synthesis method achieved a first-cycle discharge capacity of 116.3 mAh g⁻¹. -1 The initial coulombic efficiency was 87.5%, and after 45 cycles, the solid-state battery achieved a discharge specific capacity of 103.7 mAh g. -1 .
[0107] Example 8
[0108] This embodiment provides a composite cathode material for sulfide solid-state batteries with a three-dimensional ion transport network, including lithium nickel cobalt manganese oxide (LiNi). 0.8 Co 0.1 Mn 0.1 The composition consists of O2 single-crystal cathode material, Li6PS5Cl sulfide electrolyte, and conductive carbon black (SP), wherein the mass ratio of lithium nickel cobalt manganese oxide single-crystal cathode material, Li6PS5Cl sulfide electrolyte, and SP is 70:30:3.
[0109] This embodiment also provides a method for in-situ preparation of lithium nickel cobalt manganese oxide sulfide composite cathode material with a three-dimensional ion transport network using a mixed solution synthesis method. The specific steps are as follows:
[0110] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, and 111.14 mg P2S5 were simultaneously added to a mixed solution of 100 ml n-butylamine and 10 ml ethylenedithiol. The mixture was stirred at 65 °C for 2 hours. Under the strong nucleophilic force of the thioanion in the mixed solution, the Li2S, P2S5, and LiCl components were completely dissociated and dissolved in the mixed solution, resulting in a sulfide electrolyte precursor component solution.
[0111] Step 2: 626.25 mg of lithium nickel cobalt manganese oxide single crystal cathode material and 26.84 mg of SP were simultaneously added to the precursor component solution of the above sulfide electrolyte, and the mixture was magnetically stirred at 65°C for 3 hours. Under physical / chemical action, some of the sulfide electrolyte precursor components were adsorbed uniformly onto the surface of the cathode active material particles through the interaction force between TM-OPS, and a solid-liquid mixture was obtained.
[0112] Step 3: The obtained solid-liquid mixture is transferred to a vacuum tube furnace connected to a glove box filled with argon gas and vacuum dried at 90°C for 12 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min and calcined at high temperature for 15 hours to promote the pre-formation of a uniform interface buffer layer containing Li-TM-OPS components on the surface of the high specific capacity positive electrode active material. Then, crystalline sulfide electrolyte Li6PS5Cl is generated in situ in the interface buffer layer and the gaps between the positive electrode active material particles, thereby obtaining a composite positive electrode bulk material with a three-dimensional ion transport network prepared in situ by the mixed solution synthesis method.
[0113] Step 4: The obtained composite cathode material is manually ground in a glove box using a mortar and pestle for 10 minutes to obtain a composite cathode powder material in which each component is uniformly dispersed and crystalline Li6PS5Cl is uniformly coated on the surface of the interface buffer layer material and the gaps between the lithium nickel cobalt manganese oxide single crystal cathode material particles. The Li6PS5Cl electrolyte particle size is 0.2-1 μm and the coating thickness is 2-4 μm.
[0114] Step 5: Assemble the lithium nickel cobalt manganese oxide sulfide composite cathode obtained in Step 4, the laboratory-prepared Li6PS5Cl sulfide electrolyte powder material, and the lithium-indium alloy anode material into a sulfide solid-state battery in an argon-filled glove box.
[0115] Step 6: Incubate the assembled sulfide solid-state battery at 30°C and 3.0-4.4V (vs. Li). + / Li), 0.1C (1C=200mAg) -1 Charge-discharge tests were conducted under various rate conditions. The solid-state battery assembled from the composite cathode material prepared in situ using a mixed solution synthesis method achieved a first-cycle discharge capacity of 120.5 mAh g⁻¹. -1 The initial coulombic efficiency was 86.8%, and after 45 cycles, the discharge specific capacity of the solid-state battery reached 112.3 mAh g. -1 .
[0116] Comparative Example 1
[0117] This embodiment provides a composite cathode material for sulfide solid-state batteries, comprising a lithium-rich manganese-based monocrystalline cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based monocrystalline cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0118] This embodiment also provides a solid-state synthesis method for preparing lithium-rich manganese-based sulfide composite cathode materials, the specific steps of which are as follows:
[0119] Step 1: In an argon-filled glove box, 178.9 mg of lithium-rich manganese-based single-crystal cathode material, 13.42 mg of VGCF, and 268.394 mg of Li6PS5Cl were manually ground for 30 minutes using a mortar to obtain lithium-rich manganese-based sulfide composite cathode powder material prepared by solid-state method.
[0120] Step 2: Assemble the lithium-rich manganese-based sulfide composite cathode, Li6PS5Cl sulfide electrolyte powder material, and lithium-indium alloy anode material into a sulfide solid-state battery in an argon-filled glove box.
[0121] Step 3: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge and discharge tests were performed under the specified rate conditions. Figure 6 , 7 As shown, the solid-state battery assembled using a composite cathode prepared by the solid-state method has an initial discharge capacity of 70.81 mAh g⁻¹. -1 The initial coulombic efficiency was only 60.43%, and the discharge capacity after 45 cycles was only 130.65 mAh g. -1 .
[0122] Comparative Example 2
[0123] This embodiment provides a composite cathode material for sulfide solid-state batteries, comprising a lithium-rich manganese-based monocrystalline cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based monocrystalline cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0124] This embodiment also provides a method for preparing lithium-rich manganese-based sulfide composite cathode materials by solution treatment, the specific steps of which are as follows:
[0125] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, and 111.14 mg P2S5 were simultaneously added to 50 ml of ethylenediamine solution and stirred at 65 °C for 2.5 hours. It was found that the components Li2S, P2S5, and LiCl could not be completely dissociated in the ethylenediamine solution, resulting in a solid-liquid mixture of Li2S, P2S5, and LiCl in the ethylenediamine solution.
[0126] Step 2: In an argon-filled glove box, 178.9 mg of lithium-rich manganese-based single-crystal cathode material and 13.42 mg of VGCF were simultaneously added to the solid-liquid mixture of the above-mentioned Li2S, P2S5, and LiCl ethylenediamine solutions. The mixture was magnetically stirred at 60°C for 6 hours to obtain a solid-liquid mixture of lithium-rich manganese-based cathode material, sulfide electrolyte precursor components Li2S, P2S5, LiCl, and ethylenediamine solution.
[0127] Step 3: Transfer the above solid-liquid mixture to a vacuum tube furnace connected to a glove box filled with argon gas, and vacuum dry it at 80°C for 10 hours. Then, heat it to 700°C at a heating rate of 2°C / min and calcine it at high temperature for 15 hours to obtain the lithium-rich manganese-based sulfide composite cathode bulk material prepared by the ethylenediamine solution treatment method.
[0128] Step 4: The lithium-rich manganese-based sulfide composite cathode material prepared by the ethylenediamine solution treatment method is manually ground in a glove box using a mortar and pestle for 20 minutes to obtain lithium-rich manganese-based sulfide composite cathode powder material.
[0129] Step 4: The lithium-rich manganese-based sulfide composite cathode material, Li6PS5Cl sulfide electrolyte powder material, and lithium-indium alloy anode material prepared by the ethylenediamine solution treatment method are assembled into a sulfide solid-state battery in an argon-filled glove box.
[0130] Step 5: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under high-rate conditions. A sulfide solid-state battery assembled with a composite cathode prepared by the ethylenediamine solution treatment method achieved a first-cycle discharge capacity of 40.3 mAh g⁻¹. -1 The initial coulombic efficiency was 63.1%, and after 45 cycles, the discharge specific capacity of the solid-state battery was only 30.5 mAh g. -1 .
[0131] Comparative Example 3
[0132] This embodiment provides a composite cathode material for sulfide solid-state batteries, comprising a lithium-rich manganese-based monocrystalline cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based monocrystalline cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0133] This embodiment also provides a method for preparing lithium-rich manganese-based sulfide composite cathode materials by solution treatment, the specific steps of which are as follows:
[0134] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, and 111.14 mg P2S5 were simultaneously added to 10 ml of ethanethiol solution and stirred at 65°C for 2.5 hours. It was found that the components Li2S, P2S5, and LiCl could not completely dissociate in the ethanethiol solution, resulting in a solid-liquid mixture of Li2S, P2S5, and LiCl in ethanethiol solution.
[0135] Step 2: In an argon-filled glove box, 178.9 mg of lithium-rich manganese-based single-crystal cathode material and 13.42 mg of VGCF were simultaneously added to the solid-liquid mixture of the above-mentioned Li2S, P2S5, and LiCl ethanethiol solutions. The mixture was magnetically stirred at 60°C for 6 hours to obtain a solid-liquid mixture of lithium-rich manganese-based cathode material, sulfide electrolyte precursor components Li2S, P2S5, LiCl, and ethanethiol solutions.
[0136] Step 3: Transfer the above solid-liquid mixture to a vacuum tube furnace connected to a glove box filled with argon gas, and vacuum dry it at 80°C for 10 hours. Then, heat it to 700°C at a heating rate of 2°C / min and calcine it at high temperature for 15 hours to obtain the lithium-rich manganese-based sulfide composite cathode bulk material prepared by the ethanethiol solution treatment method.
[0137] Step 4: The lithium-rich manganese-based sulfide composite cathode material prepared by the ethanethiol solution treatment method is manually ground in a glove box using a mortar and pestle for 20 minutes to obtain lithium-rich manganese-based sulfide composite cathode powder material.
[0138] Step 4: The lithium-rich manganese-based sulfide composite cathode material, Li6PS5Cl sulfide electrolyte powder material, and lithium-indium alloy anode material prepared by the ethanethiol solution treatment method are assembled into a sulfide solid-state battery in an argon-filled glove box.
[0139] Step 5: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under [variable] rate conditions. The first discharge capacity was 50.1 mAh g. -1 The initial coulombic efficiency was 64.3%, and after 45 cycles, the discharge specific capacity of the solid-state battery was only 43.6 mAh g. -1 .
[0140] Comparative Example 4
[0141] This embodiment provides a composite cathode material for sulfide solid-state batteries, comprising a lithium-rich manganese-based monocrystalline cathode material, a Li6PS5Cl sulfide electrolyte, and a conductive agent VGCF, wherein the mass ratio of the lithium-rich manganese-based monocrystalline cathode material, the Li6PS5Cl sulfide electrolyte, and the conductive agent VGCF is 40:60:3.
[0142] This embodiment also provides a method for preparing lithium-rich manganese-based sulfide composite cathode materials by physical mixing, the specific steps of which are as follows:
[0143] Step 1: In an argon-filled glove box, 42.39 mg LiCl, 114.87 mg Li2S, 111.14 mg P2S5 sulfide electrolyte precursor components, 178.9 mg lithium-rich manganese-based single crystal cathode material, and 13.42 mg VGCF were physically ground in a mortar for 0.5 hours at room temperature to obtain a solid-solid mixture in which all solid phase components are uniformly mixed.
[0144] Step 2: Transfer the above solid-solid mixture to a vacuum tube furnace connected to a glove box filled with argon gas, vacuum dry at 80°C for 10 hours, then heat to 700°C at a heating rate of 2°C / min, and calcine at high temperature for 15 hours to obtain the lithium-rich manganese-based sulfide composite cathode bulk material prepared by physical mixing method.
[0145] Step 3: The above-mentioned lithium-rich manganese-based sulfide composite cathode block material is manually ground in a glove box using a mortar and pestle for 20 minutes to obtain lithium-rich manganese-based sulfide composite cathode powder material.
[0146] Step 4: Assemble the lithium-rich manganese-based sulfide composite cathode powder, Li6PS5Cl sulfide electrolyte powder, and lithium-indium alloy anode material into a sulfide solid-state battery in an argon-filled glove box.
[0147] Step 5: Incubate the assembled sulfide solid-state battery at 30°C and 2.0-4.7V (vs. Li). + / Li), 0.1C (1C=250mAg) -1 Charge-discharge tests were conducted under [variable] rate conditions. The first discharge capacity was 45.3 mAh g. -1 The initial coulombic efficiency was 59.3%, and after 45 cycles, the discharge specific capacity of the solid-state battery was only 39.5 mAh g. -1 .
[0148] In summary, this invention utilizes the strong nucleophilic effect of thioanions in a mixed solution of organic amines and organic thiols to achieve complete dissolution of the sulfide electrolyte precursor components. Then, a Li-TM-OSP (TM = Ni, Co, Mn) interfacial buffer layer is formed on the surface of the positive electrode active material particles using a mixed solution method. Crystalline sulfides are then grown in situ at the gaps between the particles and the interfacial buffer layer, constructing a composite positive electrode active material with three-dimensional ion transport network characteristics. Specifically, when ethylenediamine and ethanethiol are selected as the specific organic amine and organic thiol solvents, and the amounts of ethylenediamine and ethanethiol are fixed at 50 ml and 10 ml, respectively, the prepared sulfide solid-state battery composite positive electrode material exhibits optimal electrochemical performance.
[0149] Matters not covered in this invention are common knowledge.
[0150] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A composite positive electrode active material for sulfide solid-state batteries, characterized in that: The composite positive electrode active material is formed by generating an interface buffer layer of Li-TM-OPS with the positive electrode active material particles and the conductive agent surface using a mixed solution method, and then growing crystalline sulfides in situ in the gaps between the positive electrode active material particles and the interface buffer layer to form a three-dimensional ionic composite positive electrode active material. At the same time, in the presence of the conductive agent, the composite positive electrode active materials form an anisotropic electron transport network in a bridging manner, which is a composite positive electrode active material with a three-dimensional carrier transport network. The TM is Co, or the TM is a combination of Ni, Co and Mn; The mixed solution is a mixture of organic amine and organic thiol in a volume ratio of 100:5-40; the organic amine is one or more of ethylenediamine, n-propylamine, propylenediamine and n-butylamine, and the organic thiol is one or more of ethanethiol, ethylenedithiol, propylenedithiol, propylenedithiol, benzenethiol and p-phenylenediol.
2. The composite positive electrode active material for sulfide solid-state batteries according to claim 1, characterized in that: The mass ratio of positive electrode active material particles, crystalline sulfides and conductive agents in the composite positive electrode active material is 30-90: 70-10: 0-5.
3. The composite positive electrode active material for sulfide solid-state batteries according to claim 2, characterized in that: The positive electrode active material particles are high-specific-capacity positive electrode active material particles; the high-specific-capacity positive electrode active material particles are lithium cobalt oxide (LiCoO2) and lithium nickel cobalt manganese oxide (LiNi). 0.8 Co 0.1 Mn 0.1 O2 and lithium-rich manganese base oxides 0.5Li2MnO3·0.5LiNi 1 / 3 Co 1 / 3Mn 1 / 3 One or more of O2; the conductive agent is one or more of conductive carbon black, carbon nanotubes, vapor-grown carbon fibers, and graphene.
4. A method for preparing the composite positive electrode active material for a sulfide solid-state battery as described in claim 1, characterized in that: All precursor components required for in-situ growth of crystalline sulfides, positive electrode active material particles, and conductive agents are simultaneously added to a mixed solution. The strong nucleophilic effect of the mixed solution promotes the complete dissolution of each sulfide precursor component, forming a sulfide solid electrolyte precursor solution. The positive electrode active material particles or positive electrode active material particles and conductive agents are dispersed in the formed sulfide solid electrolyte precursor solution. After high-temperature calcination, an interface buffer layer containing Li-TM-OPS components is formed on the surface of the positive electrode active material particles. Crystalline sulfides are distributed on the surface of the interface buffer layer and between the positive electrode active material particles. At the same time, in the presence of the conductive agent, an anisotropic electron transport network is formed between the composite positive electrode active materials in a bridging manner, which is a composite positive electrode active material with a three-dimensional carrier transport network. The mixed solution is a mixture of organic amine and organic thiol in a volume ratio of 100:5-40; the organic amine is one or more of ethylenediamine, n-propylamine, propylenediamine and n-butylamine, and the organic thiol is one or more of ethanethiol, ethylenedithiol, propylenedithiol, propylenedithiol, benzenethiol and p-phenylenediol.
5. The method for preparing the composite positive electrode active material for sulfide solid-state batteries according to claim 4, characterized in that: The sulfide solid electrolyte precursor solution is one or more of sulfur-containing lithium salts, sulfur-containing phosphate salts, or sulfur-containing transition metal salts, which are added to a mixed solution and stirred at 40-80 °C for 1-5 hours to obtain the solution.
6. The method for preparing the composite positive electrode active material for sulfide solid-state batteries according to any one of claims 4-5, characterized in that: (1) Add the positive electrode active material particles and the conductive agent to the sulfide electrolyte precursor solution at a mass ratio of 30-90: 0-5, and stir the reaction at 40-80 °C for 1-5 hours to obtain a solid-liquid mixture in which the positive electrode active material particles and the conductive agent are completely dispersed in the sulfide electrolyte precursor solution. (2) The obtained solid-liquid mixture is vacuum dried at 50-100 °C for 5-15 hours and calcined at 500-800 °C for 5-20 hours. First, an interface buffer layer containing Li-TM-OPS components is formed and coated on the surface of high specific capacity positive electrode active material particles. Then, crystalline sulfides are formed in situ on the surface of the interface buffer layer and between the positive electrode active material particles by the precursor components of the sulfide electrolyte. At the same time, in the presence of a conductive agent, an anisotropic electron transport network is formed between the composite positive electrode active materials in a bridging manner. Then, the mixture is ground to obtain a composite positive electrode active material with a uniform particle size distribution and a three-dimensional charge carrier transport network, which is prepared in situ by the mixed solution synthesis method.
7. The application of the composite positive electrode active material according to claim 1, characterized in that: The application of the composite positive electrode active material for sulfide solid-state batteries as described in claim 1 in the preparation of sulfide electrolyte all-solid-state batteries.
8. A sulfide electrolyte all-solid-state battery, characterized in that: The battery contains the composite positive electrode active material for a sulfide solid-state battery as described in claim 1.
Citation Information
Patent Citations
Sulfide solid electrolyte precursor solution, and preparation method and application thereof
CN110444806A
Method for coating ternary positive electrode material with sulfide solid electrolyte
CN114267833A